Genshin Impact's Role in Preserving Chinese Cultural Heritage - Wardaya, Marina; Elizabeth, Gracelyn; Wijaya, Fenie Fedora; Lennial, Lovjoyla Belinda; Willyam, Selena Cheryl (Universitas Multimedia Nusantara, 2024)
Genshin Impact, a popular video game, has attracted attention for its success in integrating elements of Chinese Cultural Heritage into its world design. This study aims to to describe the integration of Chinese cultural heritage (CCH) in the world design of Genshin Impact, while assessing its success in encouraging players' interest in visiting China. This study used a qualitative methods approach through literature studies, surveys, and in-depth observations . The results analysis showed that Genshin Impact successfully integrated various aspects of Chinese Cultural Heritage, such as traditional architecture and natural beauty into the stunning world design; most players felt the beauty of Chinese culture in the game and expressed interest in visiting the locations that served as inspiration in the game. The findings of this study suggest that Genshin Impact has great potential as a cultural promotion tool. By presenting Chinese Cultural Heritage in an engaging and interactive format, the game succeeded in arousing players' curiosity and encouraging them to learn more about Chinese culture. In addition, Genshin Impact can also contribute to increased tourist interest in China. Keywords: game; cultural heritage; culture; tourism